(Invited) Temperature-Dependent Kinetic Study of Ammonia Oxidation Reaction on Gas Diffusion Electrodes in NH3-Saturated 1 M KOH Solutions. (26th March 2018) - Liang, Zhixiu; Song, Liang; Ma, Zhong; Zhang, Yu; Adzic, Radoslav R.; Wang, Jia X.
Abstract : Ammonia oxidation reaction (AOR) is sluggish, especially at ambient temperature. To make kinetic study in electrochemical cell more informative and relevant to the catalysts' performance in direct ammonia fuel cells (DAFCs) operating at about 100 °C, it is desirable to study the AOR kinetics at elevated temperatures. However, ammonia evaporation accelerates with increasing temperature causing decrease of ammonia concentration with time. We show here a feasible solution to this issue - let argon gas bubble through concentrated ammonia before entering the electrochemical cell so that the solution can be kept ammonia saturated and oxygen free. Repeatable AOR polarization curves were obtained at temperatures up to 60 °C. The AOR activities are characterized by the average currents at 0.5 V versus RHE measured at 20 mV s -1 in potential cycles below the potential of peak current. For PtIr/C, the PGM mass activities are 25 A g -1 at 25 °C and 225 A g -1 at 60 °C. The results for Pt/C and Ir/C and discussion of the causes for their distinct kinetic behavior will be presented at the meeting.